2022
DOI: 10.3390/ijms231912023
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of ERF Transcription Factor Family and Functional Analysis of the Drought Stress-Responsive Genes in Melilotus albus

Abstract: As an important forage legume with high values in feed and medicine, Melilotus albus has been widely cultivated. The AP2/ERF transcription factor has been shown to play an important regulatory role in plant drought resistance, but it has not been reported in the legume forage crop M. albus. To digger the genes of M. albus in response to drought stress, we identified and analyzed the ERF gene family of M. albus at the genome-wide level. A total of 100 MaERF genes containing a single AP2 domain sequence were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…Notably, all MaGT genes are very hydrophilic, and most of them are predicted to be localized in the nucleus. This may result in the need for transcription factors to regulate the transcription of downstream genes to adapt to changes in the external environment [28].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, all MaGT genes are very hydrophilic, and most of them are predicted to be localized in the nucleus. This may result in the need for transcription factors to regulate the transcription of downstream genes to adapt to changes in the external environment [28].…”
Section: Discussionmentioning
confidence: 99%
“…The article of Wei et al [ 5 ] focuses on the genome-wide identification of the ERF transcription factor family and the functional analysis of the drought-stress-responsive genes in Melilotus albus ( Ma ). The authors identified a total of 100 MaERF genes containing a single AP2 domain sequence ( MaERF001 to MaERF100 ).…”
mentioning
confidence: 99%